The Biological Parameters as an Indicators of Water Quality for a Tourism Area Spot in Jurang Sate Primary Canal Central of Lombok, Indonesia - Baiq Dini Najia Dzurrahmi; Agil Al Idrus; Lalu Japa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Jurang Sate primary canal is one of the the main irrigation canal in central Lombok whichÃÂ supplies water from the main network, namely Jangkok, Sesaot, and Keru Feeder weir to several secondary canal and to irrigated tertiary plots. The local community use the Jurang Sate Primary canal in a variety of daily activities, and nowadays it is used as a means of water tourism. The purpose of this study was to determine the water quality for ectourism area spot of the Jurang Sate primary canal based on biological parameters, namely the total Coliform bacteria, and the diversity of phytoplankton species. Measurement of coliform bacteria parameters and phytoplankton diversity was carried out ex-situ. The results showed that the total Coliform bacteria count in each sample calculated with MPN index was in the range of 170-110000 MPN/100 ml. The phytoplankton identified in this study were 24 species, 15 orders, and 6 classes. Phytoplankton species diversity index value of 1.32 (medium category). The water of the primary channel of Jurang Sate was categorized in moderately polluted. The conclusion of this research is the water of the Jurang Sate primary canal is not ideal for water tourism activity.